1994
DOI: 10.1002/mats.1994.040030104
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte/Ionomer behavior in polymer gel collapse

Abstract: SUMMARY:The theory of collapse of weakly charged polyelectrolyte gels is generalized by taking into account the possibility of counter ion trapping with the formation of ion pairs, which becomes progressively important as the gel shrinks and the dielectric constant of the gel medium decreases. A phenomenon well known in the theory of ionomers, namely the aggregation of ion pairs due to dipole-dipole interactions with the formation of multiplets, is also taken into account. These multiplets act as additional ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(158 citation statements)
references
References 16 publications
9
149
0
Order By: Relevance
“…Previous studies have indicated that the existence of such avalanche effects might lead to a new supercollapsed state. 36 However, since this state has so far not been seen under ordinary experimental conditions, we can safely assume that such higher order terms do not have any appreciable effect on the main physical conclusions of our work.…”
Section: Polyelectrolyte Gel In a Divalent Salt Solutionmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous studies have indicated that the existence of such avalanche effects might lead to a new supercollapsed state. 36 However, since this state has so far not been seen under ordinary experimental conditions, we can safely assume that such higher order terms do not have any appreciable effect on the main physical conclusions of our work.…”
Section: Polyelectrolyte Gel In a Divalent Salt Solutionmentioning
confidence: 72%
“…Numerous experiments, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] computer simulations, [23][24][25][26][27][28][29][30] and theoretical arguments [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] have established clearly that the effective charge for all polyelectrolyte systems varies as the experimental variables are changed. This effect is known to be present for a variety of polyelectrolyte systems, such as single chains, 32,46 polyelectrolyte brushes, 35 and gels, 36,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high polymer concentration the dielectric constant crosses over from that of the polar solvent to that of an organic medium (essentially polymer) [121]. If the dielectric constant is low, charges of opposite signs are not dissociated and the polymer has an ionomer behavior dominated by attractive interactions between dipoles.…”
Section: Discussionmentioning
confidence: 99%
“…20 Khokhlov and Kramarenko took the possibility of ion-pair into account. 21 Safronov et al considered the ion type dependence of the Flory-Huggins parameter. 22 English et al studied the volume transition of polyampholyte gels using Tanaka's theoretical formalism.…”
Section: Introductionmentioning
confidence: 99%